2011
DOI: 10.1021/jf200338b
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics, Phytic Acid, and Phytase in Canadian-Grown Low-Tannin Faba Bean (Vicia faba L.) Genotypes

Abstract: Thirteen low-tannin faba bean genotypes grown at two locations in north central Alberta in 2009 were evaluated to investigate the variation in seed characteristics, phenolic and phytate contents, and phytase and antioxidant activities and to elucidate the relationship of these components as a breeding strategy. Seed characteristics including color were predominantly genotype dependent. The faba bean genotypes with total phenolic content ranging from 5.5 to 41.8 mg of catechin equiv/g of sample was linearly rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 28 publications
6
62
4
Order By: Relevance
“…According to SCHOENINGER et al (2014b), when studying the color difference (ΔE) in beans of aged and pre-processed pinto group, we obtained results for this parameter between 2.24 and 14.54, so the values found in this study are among those found by the author. OOMAH et al (2011), in a study with different bean genotypes, obtained for the color difference, values of ΔE varying between 58.01 and 75.16, therefore the values for this parameter found in these studies were not as relevant as those of the author. During storage, the compounds present in the seed tegument may undergo oxidation or other chemical changes leading to new compounds that change the grain color (MARTIN-CABREJAS et al, 1997).…”
Section: Resultsmentioning
confidence: 70%
“…According to SCHOENINGER et al (2014b), when studying the color difference (ΔE) in beans of aged and pre-processed pinto group, we obtained results for this parameter between 2.24 and 14.54, so the values found in this study are among those found by the author. OOMAH et al (2011), in a study with different bean genotypes, obtained for the color difference, values of ΔE varying between 58.01 and 75.16, therefore the values for this parameter found in these studies were not as relevant as those of the author. During storage, the compounds present in the seed tegument may undergo oxidation or other chemical changes leading to new compounds that change the grain color (MARTIN-CABREJAS et al, 1997).…”
Section: Resultsmentioning
confidence: 70%
“…Immature faba bean seeds (fresh or frozen) are a favored vegetable in many countries. Like other food legumes, faba bean contains numerous phytonutrients, such as vitamins, minerals and phenolics, which contribute to the overall antioxident activities of plant foods (Oomah et al, 2011;Baginsky et al, 2013). Faba bean provides an alternative to soybean meal for animal feed in temperate regions where soybean cannot be grown.…”
Section: Crop Faba Bean (Vicia Faba L)mentioning
confidence: 99%
“…The TiCl 4 assay can and should be used together with the UV assay for selecting low V-C but high phenolic/tannin (nutritionally valuable, rich in antioxidants) genotypes in cotyledons and/or whole seeds that are immature or mature. Oomah et al (2011) determined a very high correlation between tannins and phenolic compounds in screened faba bean varieties. They measured higher levels of phenolic compounds and tannin in Snowbird relative to CDC Fatima, similar to the results observed in our TiCl 4 assay (480 nm absorbance; Figure 7).…”
Section: Ticl 4 Assay Re-evaluation Modificationmentioning
confidence: 94%